The views and experiences of Malaysian primary care doctors in managing patients with chronic low back pain: a qualitative study - Salim, Hani Syahida; Liew, Su May (Academy of Family Physicians of Malaysia, 2018)
Background: Chronic low back pain (CLBP) is a common and often difficult to treat condition in the primary care setting. Research involving in-depth exploration on the views and experiences faced by primary care doctors in managing patients with CLBP in Malaysia is limited. Objective: To explore the primary care practitioners’ views and experiences in managing patients with CLBP. Study design: A qualitative approach was employed using focus group discussions (FGD) at an academic primary care clinic in Kuala Lumpur, Malaysia. Twenty-three primary care doctors were purposively selected. Data were collected through audio-recorded interviews, which were transcribed verbatim and checked for accuracy. Data saturation was reached by the third FGD. An additional FGD was included to ensure completeness. A thematic approach using the one sheet of paper (OSOP) method was used to analyse the data. Results: Participants view managing patients with CLBP as challenging. This is mainly due to the difficulty in balancing the doctors’ expectations with the patients’ perceived expectations during consultation. Barriers identified include lack of awareness and conflicting views regarding the usefulness of the local clinical practice guideline (CPG) in clinical practice. Other barriers include time constraints and perceived lack of support from multidisciplinary teams in managing these patients. Conclusion: Managing patients with CLBP is still a challenge for Malaysian primary care doctors. Any intervention should target identified barriers to improve the management of patients with CLBP.